2008
DOI: 10.1093/annonc/mdn036
|View full text |Cite
|
Sign up to set email alerts
|

Defining prognosis for women with breast cancer and CNS metastases by HER2 status

Abstract: In our cohort of patients with breast cancer and CNS metastases, patients with HER2-positive disease treated with trastuzumab had longer times to development of and better survival from CNS metastases compared with patients with HER2-positive disease who had never received trastuzumab and patients with HER2-negative breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
137
1
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(160 citation statements)
references
References 16 publications
15
137
1
7
Order By: Relevance
“…Our study were in accordance with many studies ( Dawood et al, 2008;Moradi Marjaneh et al, 2008) that revealed PR and HER-2 do not have effect on survival, but in some studies HER-2 was a prognostic factors (Khodabakhshi et al, 2011). Protein P53 was not prognostic factor for survival.…”
Section: Discussionsupporting
confidence: 93%
“…Our study were in accordance with many studies ( Dawood et al, 2008;Moradi Marjaneh et al, 2008) that revealed PR and HER-2 do not have effect on survival, but in some studies HER-2 was a prognostic factors (Khodabakhshi et al, 2011). Protein P53 was not prognostic factor for survival.…”
Section: Discussionsupporting
confidence: 93%
“…Results from our study further illustrate that the incidence of CNS metastasis in patients with HER2-positive disease is significantly higher in patients treated with trastuzumab than in those not treated with trastuzumab (37.8 vs 25.0%, respectively, P ¼ 0.028). This finding can be explained by both the known aggressive nature and by the increased predilection to CNS metastases of HER2-positive tumours (Dawood et al, 2008). In addition, adding trastuzumab did not affect the development of BMs in HER2-overexpressing breast cancer, which is associated with the poor penetration of trastuzumab across the blood-brain barrier (BBB) and poor activity in BMs.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, despite ineffective delivery of trastuzumab imposed by the blood-brain barrier, some studies suggested that prolonged survival may also include patients who developed brain relapse while on therapy with this agent [14,24,[34][35][36][37][38][39]. For example, in the study of Lower et al [14] the mean survival in patients who developed brain relapse during trastuzumab therapy was 1,400 days, compared to 639 days in patients with brain relapse who were not applied this agent.…”
Section: Discussionmentioning
confidence: 99%